Problems with hypertensive therapy in the general practitioner’s office - Andrzejak, Ryszard; Silber, Michał; Poręba, Rafał; Kucharski, Wojciech (Przewodnik Lekarza/Guide for GPs, 2007)
Hypertension is the most common cardiovascular disease and the most common cause of development of ischaemic heart disease and cerebrovascular events. Hypertension is diagnosed in approximately thirty percent of the adult Polish population but a lot of patients are unaware of this. The fact that a huge proportion of hypertensive patients who know about their higher levels of blood pressure do not undergo therapy, or are not treated correctly, is alarming